IDENTIFICATION OF LOCAL MICROORGANISM (MOL) BIO ACTIVATOR VARIATION AS BOKASI MATERIAL - Fadhil, M.; Irfan; Sulaiman, Ismail (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
[IDENTIFICATION OF LOCAL MICROORGANISM (MOL) BIOACIVATOR VARIATIONS  AS BOKASHI MATERIAL]. Waste management is a significant problem today, particularly concerning waste generated from the processing of various products or foods. Utilizing waste serves as an essential solution to create a better and greener environment, thus providing an important breakthrough for communities and their surroundings. One of the processes for producing bokashi from food waste requires microorganisms to accelerate the waste transformation into bokashi. One such material for this process is the local microorganism (MOL) bioactivator, though MOL usage can be modified with additives like sugar to enhance the bioactivator’s effectiveness beyond that of standard MOL found in the community. This study aims to evaluate the effectiveness of MOL and EM-4 in bokashi production and their impact on soil fertility and plant productivity by identifying the population of local microorganisms with additional waste materials to improve the bioactivator’s efficiency in the bokashi production process. The study investigates bioactivator preparation, divided into four treatment groups: (M1) MOL (papaya and banana), (M2) enriched MOL (papaya, banana, and rice), (M3) a commercial bioactivator (EM-4), and (M4) a commercial bioactivator with added sugar (activated EM-4). Results after a 7-day fermentation period indicate Total Plate Count (TPC) values of M1 = 13.09 Log CFU/mL, M2 = 10.45 Log CFU/mL, M3 = 9.24 Log CFU/mL, and M4 = 10.69 Log CFU/mL. The pH values were similar across treatments and did not vary significantly (M1 = 4.09; M2 = 4.10; M3 = 3.95; and M4 = 3.91).